2018
DOI: 10.21037/tcr.2018.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP) and immunosuppressive biomarker profiles of seven head and neck squamous cell carcinoma (HNSCC) cell lines

Abstract: Background: Biomarkers like programmed death ligand-1 (PDL1) have become a focal point for immunotherapeutic checkpoint inhibition in head and neck squamous cell carcinoma (HNSCC). However, it’s only part of the total immunosuppressive biomarker profile of HNSCC cells. Matrix metalloproteinases (MMPs) are enzymes that break down the basement membrane allowing cancer cells to metastasize and play an important role in the tumor microenvironment. MMPs can also activate certain cytokines, growth factors, and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In HNSCC, different results on IDO1 are documented, and expression is heterogeneous among different HNSCC cell lines. Of note, IDO1 abundance of primary resection specimen and cultured cells seems to be independent from anatomical site and HPV status (40). Still, IDO1 is a useful marker for progression of in oral squamous cell carcinoma (41).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In HNSCC, different results on IDO1 are documented, and expression is heterogeneous among different HNSCC cell lines. Of note, IDO1 abundance of primary resection specimen and cultured cells seems to be independent from anatomical site and HPV status (40). Still, IDO1 is a useful marker for progression of in oral squamous cell carcinoma (41).…”
Section: Discussionmentioning
confidence: 95%
“…Indirect effects of TRP metabolism include interference with other biological functions like migration, angiogenesis, and cell growth regulation (18,40). To investigate the influence of anticancer drugs on TRP catabolism, we performed a comprehensive analysis using conventional chemotherapy (TMZ, 5-FU, Cisplatin, Gemcitabine) and targeted drugs (Cetuximab, Dinaciclib).…”
Section: Discussionmentioning
confidence: 99%
“…Bates et al found that PD-L1 was present in differing concentrations on the surface of HNSCC cell lines in Table 1 by ELISA, and we summarized this information in Table 2 [10]. PD-L1 concentrations in cell lysates ranged from 79.67 to 539.79 pg/mL.…”
Section: Resultsmentioning
confidence: 94%
“…HNSCCs arise through the accumulation of genetic and epigenetic changes in genes acting in cancer-associated signaling pathways [1,7,8]. HNSCC cells produce a variety of immunosuppressive cytokines, chemokines, and biomarkers [9,10]. Among these is programmed death-ligand 1 (PD-L1) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation